2015
DOI: 10.1016/j.pec.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, feasibility and effectiveness of an eHealth behaviour intervention using self-regulation: ‘MyPlan’

Abstract: Objective: The study aims to evaluate the acceptability, feasibility and effectiveness of the eHealth intervention 'MyPlan', which targets health behaviour in adults. Methods: Flemish adults were randomly allocated to a control (n=155), or one of three intervention groups: a physical activity (PA) (n=158), a fruit intake (n=161) or a vegetable intake group (n=48). PA, fruit or vegetable intake were measured at the start and after 1 month. Results: Adults with low education, and over 40 years evaluated the pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…A review of the relatively small number of studies which examine acceptability and feasibility, showed that definitions are often not provided (e.g., [63][64][65]) and have not been applied to the context of urban landscape management. We adapted the work by Johnson et al [62], who conceptualise the meaning of acceptability and feasibility in their 'Evaluating Strategy' for application in different contexts.…”
Section: Measuring Acceptability and Feasibilitymentioning
confidence: 99%
“…A review of the relatively small number of studies which examine acceptability and feasibility, showed that definitions are often not provided (e.g., [63][64][65]) and have not been applied to the context of urban landscape management. We adapted the work by Johnson et al [62], who conceptualise the meaning of acceptability and feasibility in their 'Evaluating Strategy' for application in different contexts.…”
Section: Measuring Acceptability and Feasibilitymentioning
confidence: 99%
“…A further task in Step 4 is to test the feasibility, acceptability, and user-friendliness of the intervention [ 23 , 47 ]. Therefore, a specific study was conducted to address these issues, and its results are reported in a separate publication [ 48 ]. Briefly, 194 adults who used the MyPlan 1.0 intervention filled out an online questionnaire containing items about quality, user-friendliness, and applicability of the content and information architecture (ie, organization and delivery of the content) of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…MyPlan 1.0 is a web-based intervention to promote PA and fruit and vegetable intake in the general population, and has been tested in general practice. The programme has shown to be effective in improving healthy behaviour [42][43][44]. However, high attrition rates were observed and researchers experienced problems with the implementation by general practitioners [42][43][44].…”
Section: Interventionmentioning
confidence: 99%
“…The programme has shown to be effective in improving healthy behaviour [42][43][44]. However, high attrition rates were observed and researchers experienced problems with the implementation by general practitioners [42][43][44]. Therefore, the programme has been further developed into MyPlan 2.0, which participants can use autonomously at home.…”
Section: Interventionmentioning
confidence: 99%